Yerba Mate as a Settler Crop: From the Decline of Native Herbs to the Rise of Introduced Species - Zang, Laura Mabel (Universidad del Pacífico, 2020)
From the policies aimed at preserving native herbs in the second half of the 19th century to the dissemination of introduced herbs at the beginning of the 20th, the colonization of the present-day Argentine province of Misiones was closely linked to yerba mate. After the War of the Triple Alliance (1865-1870), the national government became more aware of the strategic location of Misiones and expanded its knowledge of the bountiful natural resources the province possessed. This led to the creation of the National Territory of Misiones in 1881 and the implementation of government policies for the colonization of the area by European immigrants.